Memory of the wound : An attempt to interrogate invisible space (Raparin Journal of Humanities (RJH), 2020)
The power of silence, however, it might attend an invisible discourse framework, it goes further to the sphere of killing the opportunity of exploring the invisibility codes. Exploring the space that has been explored previously, there was a simple narrative of the victims’ stories, that could help the researcher go much deeper through different kinds of concepts that could help in the interpretation process, or create an intentional approach for the sake of the victims' subjectivities and opening wider space for its appearance.In other words, to get out of the limitations of silence we must appropriate several terms from different context to help us face its hegemony and embarking in its strong boundaries. For instance, when we simply look at an image, we do not know the intention or purpose of the image (photograph in particular) is the process of perpetuating the moment of taking it, or to freeze the time in the moment of any process. We do not look at the circumstances and the situation that produces the image, as far as our focus goes to the faces and components within the image. This mainstream and simple comprehension is a clear sign of a lack of understanding to the image’s language. That language helps to show what is touring inside who has been captured, who simply says: I was there.This study tries to find the keys that give the power of expression to the image, so that it can represent the wounded’s memory, therefore, starts to convey it through a carefully deliberated process from invisible to visible, from narrative to imagery.Dealing with the memory of wounds spreading on the Kurdish body needs a different type of approach, in a way that has not been explored previously. Explore through different means away from the prevalent and familiarity.The researcher believes that taking benefit from the experience of others in the process of representing the wounded can help in the elimination of hesitancy domination and incursion into other more open spaces by exploring a set of criteria and factors that form other extents of expression such as motion picture, cinema for example.From this standpoint, we find that the process of representing the memory of the victims in the massacres of the Jews (The Holocaust) is the most successful process during the last century until nowadays. Therefore, taking into account how to take advantage of the methods and the forms that has been used in the Holocaust imagery process can take us to a broad and informed horizon.This research tries to explore a way that can help the victims to get rid of psychological constraints and express themselves through a trustable medium that could be cinema. In the case of Kurds, exploring that type of cinema which can enhance the victims to narrate their stories without any restrictions.